
Answer:  A ∪ B = {a, b, c, d}
        (A ∪ B) ∪ C =  = {a, b, c, d, e}
        B ∪ C =  = {a, b, d, e}
        (B ∪ C) ∪ A  =  = {a, b, c, d, e}
Step-by-step explanation:
A = {a, b, c} Â Â Â B = {a, b, d} Â Â Â Â C = {b, d, e}
Union means "to join" so combine the sets to form a union.
A ∪ B = {A & B}
     = {a, b, c & a, b, d}
     = {a, b, c, d}      because we do not need to list a & b twice
(A ∪ B) ∪ C = {(A ∪ B) & C)
         = {a, b, c, d & b, d, e}
         = {a, b, c, d, e}   because we do not need to list b & d twice
B ∪ C = {A & B}
     = {a, b, d & b, d, e}
     = {a, b, d, e}      because we do not need to list b & d twice
(B ∪ C) ∪ A = {(B ∪ C) & A)
         = {a, b, d, e & a, b, c}
         = {a, b, c, d, e}   because we do not need to list a & b twice